A Study of the Effect of Ethamsylate (Dicynene) on the Bleeding Time, von Willebrand Factor Level and Fibrinolysis in Patients with von Willebrand’s Disease - Hutton, Ronald A; Hales, Mary; Kernoff, Peter B A (Thrombosis and Haemostasis, 1988)
Nine patients with clinically moderate or severe Type I von Willebrand’s disease were treated for 2 weeks with ethamsylate (2 g/day in four equal doses) and with a matched placebo in a randomised double-blind trial. Template bleeding time, von Willebrand factor activity (ristocetin co-factor) and antigen, euglobulin lysis time and type I tissue plasminogen activator inhibitor were determined before and at the end of each treatment period. None of these parameters showed any significant change attributable to ethamsylate. Thus, despite the fact that five patients thought subjectively that their bleeding symptoms improved during ethamsylate treatment compared to only one while on placebo, we obtained no evidence that the drug was of benefit to patients with von Willebrand’s disease
Keywords: Bleeding time; von Willebrand factor; Fibrinolysis